English grammar in use : a reference and practice book for intermediate learners of English : without answers - Murphy, Raymond, 1946- (Cambridge, UK ; New York : Cambridge University Press, 2012)
English Grammar in Use Fourth edition is an updated version of the world's best-selling grammar title. It has a fresh, appealing new design and clear layout, with revised and updated examples, but retains all the key features of clarity and accessibility that have made the book popular with millions of learners and teachers around the world.
Includes index.
Keywords: Engels -- Grammatica; English language -- Textbooks for foreign speakers; English language -- Grammar -- Problems, exercises, etc; English language -- Grammar; Taalkunde -- Engels